Antifungal prophylaxis in pediatric lung transplantation: An international multicenter survey. (June 2014) - Mead, Lee; Danziger‐Isakov, Lara A.; Michaels, Marian G.; Goldfarb, Samuel; Glanville, Allan R.; Benden, Christian; ,
Abstract Fungal infections create a significant risk to pediatric lung transplant recipients. However, no international consensus guidelines exist for fungal infection prevention strategies. It was the aim to describe the current strategies of antifungal prophylaxis in pediatric lung transplant centers. A self‐administered, web‐based survey on current practices to prevent fungal infection was circulated to centers within the IPLTC. Twenty‐one (88%) IPLTC centers participated, predominantly from Europe and the US. More than 50% of respondents perform adult and pediatric lung transplant operations. Twenty‐four percent use universal prophylaxis, 28% give prophylaxis to all patients but stratify the antifungal coverage based on pretransplant risk, and 48% target prophylaxis to only the children with CF or pretransplantation fungal colonization. Commonly, centers aim to target Aspergillus and Candida infection. Monotherapy with either voriconazole or inhaled amphotericin B is used in the majority of centers. Institutions utilize prophylactic therapy for variable time periods (40% 3–6 months; 30% ≥12 months). Alternative drugs were prescribed for lack of tolerance, toxicity, or positive surveillance culture. TDM (itraconazole/voriconazole) was used in 86% of centers. The survey revealed a wide range of antifungal prophylaxis strategies as current international practice in pediatric lung transplant recipients.